Leader and leadership in international companies - MILITARU, Mădălina (Annals of Spiru Haret University. Economic Series, 2010)
Within the actual global economy context, competition will be complex, challenging and full of competitive opportunities and threats. Effective leadership practices can help international corporations improve performance while competing in turbulent and unpredictable environments. Leadership has been defined in many different ways, but most definitions share the assumption that it involves an influence process focused on facilitating the performance of a collective task.